2017
DOI: 10.1177/147776061703300405
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Devulcanised Rubber in Fresh Rubber Compounds: Impact of Filler Correction on Vulcanisate Properties

Abstract: Carbon black filled natural rubber (NR) vulcanisate with known composition and properties were mechanically devulcanized by shearing in a laboratory two roll mill. The efficiency of devulcanisation was determined through crosslink density measurements. In order to simulate the end-of-life rubber products, mechanical devulcanisation of samples aged at standard laboratory conditions were also carried out. The devulcanized rubber prepared from un-aged and aged samples were incorporated in fresh compounds at thre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 28 publications
0
9
0
Order By: Relevance
“…Table 3 and plotted in Figure 4 for the 700 ℃ -filled and 600 ℃ -filled vulcanisates increases with increase in the filler loadings. This result is expected because as more filler particles enters the rubber, the elasticity of the rubber chain was reduced, resulting in more rigid vulcanisates (Joseph et al, 2017). The hardness results for 700 ℃ wood flour-filled vulcanisates are higher than those for the 600 ℃-filled vulcanisates.…”
Section: Mechanical Properties Of Productmentioning
confidence: 92%
“…Table 3 and plotted in Figure 4 for the 700 ℃ -filled and 600 ℃ -filled vulcanisates increases with increase in the filler loadings. This result is expected because as more filler particles enters the rubber, the elasticity of the rubber chain was reduced, resulting in more rigid vulcanisates (Joseph et al, 2017). The hardness results for 700 ℃ wood flour-filled vulcanisates are higher than those for the 600 ℃-filled vulcanisates.…”
Section: Mechanical Properties Of Productmentioning
confidence: 92%
“…Additionally, many authors have found a reduction in mechanical properties upon replacement of the elastomer matrix with GTR (except for certain styrene butadiene rubber [SBR] blends), 25 and even filler‐like (rather than matrix‐like) properties for recycled rubbers that have been blended with virgin materials 1,3,14,26–29 . Reduced mechanical properties, particularly tensile strength and elongation at break (EB), of recycled rubber/natural rubber blends are widely reported, and those that do match virgin‐like properties contain low‐recyclate loadings <15 wt% 21,30–34 …”
Section: Introductionmentioning
confidence: 99%
“…It is worth highlighting that GTR, and devulcanized rubber generally, is dissimilar to virgin natural rubber (vNR) in many ways. These recyclates contain significant concentrations of fillers and additives, as well as being partially crosslinked 14,18,25,34–36 . The bonds that have been broken by devulcanization exist in a state that is more similar to a partially vulcanized rubber than a virgin material 6,35,37 .…”
Section: Introductionmentioning
confidence: 99%
“…Some studies have reported a loss of mechanical properties by incorporating ground rubber wastes into raw rubber matrix, since the interaction between the vulcanized and the raw rubber was weak [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…However, the proposed process is advantageous, considering a reduction in costs. In addition, some authors have used the devulcanization process in recycled rubbers before producing composites or polymeric blends to increase the interaction between the phases due to the better dispersion of the recycled rubber particles in the polymeric matrix, which results in a more refined phases morphology and improvements in the mechanical properties [13,[16][17][18][19][20][21][22].…”
Section: Introductionmentioning
confidence: 99%